A discovery of the genus Philoplitis Nixon, 1965 (Hymenoptera: Braconidae: Microgastrinae) in Vietnam, with description of two new species - Khuat, Dang Long; Quynh Mai, Pham; Hiep, Nguyen Duc; Thi Hoa, Dang; Dinh Duong, Tran (Academia Journal of Biology, 2025)
The small microgastrine genus Philoplitis Nixon, 1965 from Vietnam is newly recorded. As a result, two new species are described and fully illustrated, viz. Philoplitis ipunctatus Long, sp. nov. and Philoplitis cariniferus Long, sp. nov.. Additionally, the genus Philoplitis is recorded for the first time for Vietnam, and the comparative characters of Philoplitis species summarized in a table.